Flextime and Gen Z Work-Life Balance: The Moderating Roles of Job Crafting and Boundary Management - Abdul Kadir Alamudi; Maulidyah Amalina Rizqi (Management Analysis Journal, 2026)
This research study examines the effectiveness of flextime policy on the Work-Life Balance (WLB) of Generation Z employees by evaluating the dual moderating roles of Job Crafting (an expansive strategy) and Boundary Management Strategies (a protective strategy). Flexible work arrangements (flextime) are often assumed to be the ideal solution for achieving Work-Life Balance (WLB). However, for Generation Z employees, this autonomy frequently triggers the "Autonomy Paradox," which blurs the boundaries between work and personal time. Using an explanatory quantitative approach, a survey was distributed to 400 Generation Z employees across various industries in Indonesia who have access to flexible work arrangements. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results indicate that flextime policy, in isolation, does not significantly affect WLB. Furthermore, Job Crafting behavior does not strengthen this relationship and instead risks triggering self-exploitation. Conversely, Boundary Management Strategies significantly strengthen the positive impact of flextime on WLB. The conclusion of this study emphasizes that time flexibility requires individuals' ability to establish firm boundaries (psychological detachment). As a managerial implication, organizations are advised not merely to provide time autonomy but also to facilitate digital boundary management training.